Har antalet naturvärdesträd i Sverige förändrats mellan 1999-2009? - Karlsson, Ida (2010)
Forestry and forest products are vital components of the Swedish economy but the forest is also important for recreation, hunting, out-door life and conserving biodiversity. The Swedish Forest Act has two equally important objectives, production and environmental protection. Polytax is the Swedish Forest Agency´s inventory programme which monitors progress toward the two objectives in connection with regeneration fellings. It includes data on environmental protection measures taken in connection with regeneration fellings. 30 § of the Swedish Forestry Act and related regulations specify the demands for conserva-tion of nature. Modern forestry creates monocultures and to counteract that Swedish fore-stry has introduced a number of biodiversity-orientated management practices. One of them is Green-tree retention cutting (GTR) which is a modification of traditional clear-cutting and implies that some living trees are left on the cut area.